THE RELATIONSHIP BETWEEN NURSE CARING AND PATIENT SATISFACTION IN THE GENERAL SURGERY WARD OF THE PURUK CAHU REGIONAL GENERAL HOSPITAL - Pratama, Ari Sandy; Tasalim, Rian; Rahman, Subhannur; Wijaksono, Muhammad Arief; Rusadi, Framita (HEARTY, 2025)
Nurse caring is a crucial aspect of healthcare services that significantly impacts patient satisfaction. In the Regional General Hospital Puruk Cahu, the general surgery ward experiences a high number of patient visits, highlighting the importance of understanding the role of nurse caring in influencing patient satisfaction. This study aims to analyze the relationship between nurse caring and patient satisfaction levels in the general surgery ward of the Regional General Hospital Puruk Cahu. This study employed a descriptive correlational quantitative approach with a cross-sectional design. Respondents consisted of adult patients treated in the general surgery ward of the Regional General Hospital Puruk Cahu during September–October 2024. Data were collected using questionnaires on nurse caring and patient satisfaction and analyzed with correlation tests. The majority of respondents (63.3%) rated nurse caring as very high, and 53.3% expressed feeling very satisfied with the care provided. However, the correlation test results indicated no significant relationship between nurse caring and patient satisfaction (p-value = 0.407). While nurse caring was perceived as very high by patients, there was no significant correlation with their satisfaction levels. Other factors may influence patient satisfaction, emphasizing the need to enhance nurse caring quality through targeted training and a holistic approach to achieve optimal nursing care services.